RED BEET VARIETIES OF VNIISSOK’S BREEDING - M. I. Fedorova; S. A. Vetrova; V. A. Zayachkovskiy; V. A. Stepanov (Овощи России, 2016)
Nine red beet varieties of the VNIISSOK’s breeding are described in the article. The methods of its development, maintenance, utilization in the breeding programs are presented. The cultivars «Bordo odnosemyanaya», «Nezhnosty», «Lyubava», «Gaspadinya» are the sources of the separately fruiting. The breeding of red beet based on fertility and cytoplasmic male sterility is conducted. The best sources for heterosis are cv. «Nezhnosty», «Odnorostkovaya», «Lyubava», «Gaspadinya». The best sources for early-ripening are cv. «Nesravnennaya A-463», «Gribovskaya ploskaya», «Podzimnyaya A-474». Because of the high adaptability, the cv. «Bordo 237» can be recommended for breeding programs in all regions of Russia. The volume of sales and seed production of these varieties are shown.